Sertão de Pedra e Argila: Tradição, Ruptura e Modernidade no Romance Galileia, de Ronaldo Correia de Brito - Vasconcelos, Carlos Roberto Nogueira de (2013)
The aim of this dissertation is to demonstrate how Ronaldo Correia de Brito, in his novel Galileia (2008), does a review of the hinterland in its spatial and cultural representation. In this literary work, the country space is shown as a territory invaded by new technologies, a fact that produces conflicts between tradition and modernity, allowing us to analyze, in this research, the clash between these forces and the changes caused by globalization on the individual people, on the family and on the society as a whole. In this context of clashes between the traditional hinterland and the new technologies, the novel Galileia shows points that unfold in a transgression of the family traditions limits: the decline of patriarchy, the subtle feminine revolution, homosexuality, incest, adultery. The novel also dialogues to the Bible, that is a permanent source of indoctrination and sacredness of the West, but also instigates ruptures, suggests profanities and uncovers a centuries-old tradition of Rego Castro’s family, that represents the inland family tradition in the novel. Modernity is presented as spontaneous factor, or as a consequence, represented through the presence of the computer and Internet cafes, the changing in established practices and the replacement of clay and copper by acrylic and plastic in the household items manufacturing. For a better development of these discussions, it was essential a critical review of some theoretical constructs such as identity and memory, which have become as important content and structural elements of the novel. About the problem of identity, it was observed that it embodies the discussion of ethnicity, even manifested in the book by the presence of the Indian and Jewish ethnicity as elements of miscegenation in the northeastern Brazilian hinterland. Regarding the study of memory, it had great importance for the analyzes in this paper the concept of "identity memory", a term developed by Janine Ponty and that was discussed by Joel Candau in the book Memory and Identity (2012). From the discussion of identity, memory and other concepts, including the literary regionalism, it was revealed that Ronaldo de Brito, in Galilee, discusses, and even denounces (but without raising flags), the unavoidable consequences of the modernity, of the capitalism that buys the honor, of the disarticulation of the family as it is traditionally known, of childhood raped on the street or in the shelter of home, of the famine caused not only by the drought but also by the unequal distribution of wealth. Interpret this antagonism of forces justifies this research.